Fe3C‐Co Nanoparticles Encapsulated in a Hierarchical Structure of N‐Doped Carbon as a Multifunctional Electrocatalyst for ORR, OER, and HER. (15th May 2019) - Yang, Chun Cheng; Zai, Shi Feng; Zhou, Yi Tong; Du, Li; Jiang, Qing
Abstract: Rational design of non‐noble metal catalysts with robust and durable electrocatalytic activity for oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) is extremely important for renewable energy conversion and storage, regenerative fuel cells, rechargeable metal–air batteries, water splitting etc. In this work, a unique hybrid material consisting of Fe3 C and Co nanoparticles encapsulated in a nanoporous hierarchical structure of N‐doped carbon (Fe3 C‐Co/NC) is fabricated for the first time via a facile template‐removal method. Such an ingenious structure shows great features: the marriage of 1D carbon nanotubes and 2D carbon nanosheets, abundant active sites resulting from various active species of Fe3 C, Co, and NC, mesoporous carbon structure, and intimate integration among Fe3 C, Co, and NC. As a multifunctional electrocatalyst, the Fe3 C‐Co/NC hybrid exhibits excellent performance for ORR, OER, and HER, outperforming most of reported triple functional electrocatalysts. This study provides a new perspective to construct multifunctional catalysts with well‐designed structure and superior performance for clean energy conversion technologies. Abstract : A hybrid material of Fe3 C‐Co/NC is synthesized through a facile template‐removal method, where Fe3 C and Co nanoparticles are encapsulated in a nanoporous N‐doped hierarchical structure integrating 1D carbon nanotubes and 2D carbon nanosheets. As a multifunctional electrocatalyst, such a hybrid exhibits superior catalytic performances for oxygen reduction reaction, oxygen evolution reaction and hydrogen evolution reaction simultaneously.